(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article aims to create a comfortable and harmonious urban environment by applying nationalism and increasing the artistry of small architectural forms (water elements, seats, garbage cans, umbrellas, parking spaces, lighting, fences) in the environment design of tourist neighborhoods. The variety of buildings, artistic and aesthetic qualities, creation of proportional parts of the city, problems of touristic intersections and integral connection of streets, artificial and natural recreation areas and water areas were considered.